Exploring External Factors Affecting the Intention-Behavior Gap When Trying to Adopt a Sustainable Diet: A Think Aloud Study - Fink, Leonie; Strassner, Carola; Ploeger, Angelika (Frontiers in Nutrition, 2021)
Not least from an ecological and health perspective, it can be posited that a broader part of consumers should practice sustainable diets. People who are already willing to do so are often confronted with the intention-behavior gap, caused by a range of internal and external factors. To eliminate these barriers requires a deeper and more comprehensive understanding of these factors and their interplay. Therefore, a think aloud study with 20 adult German participants was conducted to explore the four chosen external factors of availability, education, advertising and price. Furthermore, questionnaires for all four factors were handed out and a follow-up interview was conducted to gain additional qualitative data. Results show that these four external factors seem to have a major impact on the intention-behavior relation. According to the participants all factors interact in some way with other internal and external factors, making practicing sustainable diets a complex activity. In conclusion, the four external factors availability, education, advertising and price need to be addressed by various stakeholders within our food systems in order to move forward in the process of making sustainable diets practicable and sustainable food systems firmly established.